PROBLEM PENILAIAN PEMBELAJARAN PAI DALAM KONTEKS AUTENTIK ASESMEN - Pratama, M Arifin; Cahyani Lintang, Hatimi; Dhafin, Muhammad; Prastika, Imel; Abdurrahmansyah, Abdurrahmansyah (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to examine the problems and strategies for strengthening the implementation of authentic assessment in Islamic Religious Education (PAI) learning within the Merdeka Curriculum era. The research employs a qualitative approach through a literature review that analyzes books, scientific journals, and educational policy documents. The findings indicate that authentic assessment plays a crucial role in evaluating students’ abilities comprehensively, encompassing cognitive, affective, and psychomotor aspects integrated with real-life contexts and oriented toward the formation of Islamic character. However, its implementation still faces various challenges, including limited teacher understanding, difficulties in developing assessment instruments, and the dominance of conventional evaluation systems. Therefore, strengthening strategies are needed through teacher competency enhancement, institutional support, and a paradigm shift in assessment practices so that authentic assessment can be implemented effectively, sustainably, and in alignment with the holistic learning principles of Islamic Religious Education.